MECHANICAL INSTABILITY NEAR THE STISHOVITE-CACL2 PHASE TRANSITION: IMPLICATIONS FOR CRYSTAL PREFERRED ORIENTATIONS AND SEISMIC PROPERTIES - Cordier P.; Mosenfelder J.L.; Mainprice D. (My University, 2004)
Deformation experiments have been performed on polycrystalline stishovite at 14 GPa and 1300°C in a multi-anvil press. The easy slip systems have been determined by Transmission Electron Microscopy. We found [001]{100} and [001]{110} with minor slip in the direction. Analysis of the elastic energy of these slip systems together with previously reported systems in as-grown stishovite reveals that easy glide [001]{100} and [001]{110} systems are unaffected by the stishovite to CaCl2 transformation, whereas the energy of {11¯0} system decreases to zero at the transition, which is symptomatic of a plastic instability. We have used the visco-plastic self-consistent (VPSC) model to simulate the crystal preferred orientation (CPO) of polycrystalline stishovite in simple shear. The CPO in stishovite stability field shows a strong alignment of [001] axes parallel to direction of maximum finite strain (X) and a girdle of [100] normal to X. At conditions close to the transition, simulated by making the CRSS of [110](110) equal to easy glide [001] systems, the CPO were similar to the previous case, but slightly weaker. At the transition, simulated by making the {110} systems the only easy glide systems, the CPO of [001] axes is very weak. The anisotropic seismic properties were calculated from the CPO. In the stishovite stability field at a pressure of 21 GPa the Vp maximum is parallel to X and Vp minimum parallel to Z with an anisotropy of about 13%. The shear wave splitting has a maximum in a girdle normal to X with anisotropy of 5 to 8%. Calculations near the phase transition at a pressure of 48 GPa for CPO with easy {110} and [001] systems showed similar patterns to those at 21 GPa except that S wave anisotropy was stronger (11-18%). In conditions at the phase transition where {110} are the only easy glide systems, the seismic properties are very different, with Vp almost isotropic with anisotropy of 1.8% and a relatively low anisotropy of S waves with a maximum shear wave splitting of 4.5% in a single peak parallel to Z.